On the geographic variation of Pinus cembra in the Alpine Mountains - R. Th. Klumpp (Annals of Forest Research, 2013)
Swiss stone pine (Pinus cembra L.) populations from all over the Alpine mountains were studied, in order to give the first report on the geographic variation of Swiss stone pine. Bud samples were taken along 12 different transects and isozyme analysis was applied. Altogether, 14 enzyme systems (22 scored gene loci) were analyzed. Average number of alleles per locus was low (1.4) in comparison to other tree species and did not vary significantly amongst populations. Observed heterozygosity showed extraordinary low values, with an average of 7.1% and reaching highest values of 8.2% in the central Alpine mountains (Switzerland). The findings are discussed in the light of earlier results regarding different pine species of the subsection Cembrae.